CAP-ONES: an emergency notification system for all. (12th February 2010) - Malizia, Alessio; Acuna, Pablo; Onorati, Teresa; Diaz, Paloma; , Ignacio Aedo
In this paper, we present an ontology-based system for managing emergency alert notifications. Our purpose is to generate emergency alerts that are accessible to different kinds of people, paying special attention to more vulnerable collectives like impaired people. By adapting alerts to different devices and users, we can allow Emergency Management Systems (EMSs) to communicate with collectives like blind or deaf people who otherwise are unreachable by usual channels. Moreover, if we consider the constraints imposed by the nature of the emergency situations, we can also improve the information transmission to cope with situational disabilities (e.g., smoke during a fire can cause low vision problems). We centred our system architecture on two characteristics: 1) an ontology that codifies knowledge about accessibility, devices, disabilities, emergencies and media so the alert notification can be tailored according to different parameters, 2) an open standard like the Common Alerting Protocol (CAP) that enables our system to interoperate with other existing systems.